GENDER FEATURES OF THE STRUCTURE OF COLON EPITHELIAL NEOPLASMS - Короткевич, Алексей Григорьевич; Жилина, Наталья Михайловна (Medicine in Kuzbass, 2024)
The aim of the research – the article is devoted to the evaluation of the structure of epithelial neoplasms in different parts of the colon due to the gender of the patient. Materials and methods. A retrospective, pooled analysis of 3086 videocolonoscopies from 2019-2020. Results. The total frequency of detected neoplasms amounted to 1431 in 980 patients (31.8 %). Assessment of the frequency of detection of nonvillous adenomas by levels of the colon revealed significant gender differences in the cecum, descending colon, and rectum. The frequency of such adenomas had no significant level-by-level differences. Villous adenomas and carcinomas had no gender differences , their frequency in the sigmoid colon and rectum exceeded that in the proximal colon. The frequency of LST also had no gender differences, but their localization in the ascending, transverse and sigmoid colon exceeded that in other parts. The structure of epithelial neoplasms had significant gender differences in the cecum, descending colon and rectum. Conclusion. There are gender differences in the structure of tumors in the blind, descending and rectum. No significant differences in the overall frequency of diagnosis of colorectal malignant neoplasms by gender were found.